2015
DOI: 10.1007/s00427-015-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and phylogenetic analysis of fifteen NtabSPL genes in Nicotiana tabacum L. cv. Qinyan95

Abstract: Fifteen SPL (SQUAMOSA PROMOTER BINDING PROTEIN-LIKE) genes were identified and characterized in Nicotiana tabacum L. cv. Qinyan95. The exon-intron structures of these genes were determined according to the coding sequences confirmed by RT-PCR and the genomic DNA sequences downloaded from the databases in Sol Genomics Network, and thirteen of them were found to carry the response element of miR156. To elucidate the origin of the validated NtabSPL genes, multiple alignments of the nucleotide sequences encompassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The statistical significance of pairwise differences in size was assessed via Tukey’s ‘Honest Significant Difference’ (HSD) with adjustment for the multiple comparisons as implemented in R [ 75 ] (Additional file 5 ). To avoid potential confounding effects among groups due to size in our analyses, we used a pooled within-group multivariate regression of the Procrustes coordinates on centroid size [ 76 ]. The statistical significance of the relationship between the shape variables and the centroid sizes was assessed by a permutation test with 10,000 rounds of random permutations [ 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical significance of pairwise differences in size was assessed via Tukey’s ‘Honest Significant Difference’ (HSD) with adjustment for the multiple comparisons as implemented in R [ 75 ] (Additional file 5 ). To avoid potential confounding effects among groups due to size in our analyses, we used a pooled within-group multivariate regression of the Procrustes coordinates on centroid size [ 76 ]. The statistical significance of the relationship between the shape variables and the centroid sizes was assessed by a permutation test with 10,000 rounds of random permutations [ 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…To avoid potential confounding effects among groups due to size in our analyses, we used a pooled within-group multivariate regression of the Procrustes coordinates on centroid size [ 76 ]. The statistical significance of the relationship between the shape variables and the centroid sizes was assessed by a permutation test with 10,000 rounds of random permutations [ 76 , 77 ]. There was a significant effect of size on shape ( P- value = 0.002) and the regression of shape on centroid size accounted for 3.6% of total shape variation.…”
Section: Methodsmentioning
confidence: 99%
“…Functional morphology is therefore a compromise between adaptive forms and possible forms [ 1 ] given the organism’s evolutionary history [ 2 ]. The range of possible adaptive forms is also dictated by what morphological changes can be produced by intrinsic processes such as development or allometry) [ 3 , 4 ]. In particular, allometry—the disproportionate shape change of a trait due to a change in body size—plays a key role in shaping the evolution of new forms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutations and the composition of the calmodulin intergenic spacer in Leishmania species have been studied as a molecular target that might have taxonomic value [ 25 ]. Moreover, Karabinos [ 26 ] found that CaM-like proteins of C. elegans arose from a CaM ancestor through repeated gene duplications, fusions and sequence divergence. In E. granulosus , CaM-like proteins showed a low identity with EgCaM; therefore, it would be meaningful to explore the relationships between CaM and CaM-like genes when more homologs of cestodes are included in the future.…”
Section: Discussionmentioning
confidence: 99%